Hyper IgG4-Related Disease Presenting with Orbital Tumor and Immune Deficiency - Caroline G. Olson; Nancy Y. Olson (Case Reports in Immunology)
We report a case of IgG4-RD in a patient with high IgG4 levels, low functional antibodies, and low IgM levels. He presented with bilateral orbital pseudotumors and, after initial improvement on corticosteroids, relapsed with recurrent pleural effusion and pelvic pseudotumor. He had a grossly elevated serum IgG (1905 mg/dl) with elevations in all IgG subclasses but marked elevation in IgG4 (412 mg/dl), low IgM, and low pneumococcal antibodies. Orbital mass biopsy showed polyclonal lymphocytic infiltration and increased IgG4 plasma cells. The patient was started on prednisone and tried several immunosuppressive medications including mycophenolate mofetil, methotrexate, hydroxychloroquine, and azathioprine with decrease in size of the orbital pseudotumor. During a period when the patient stopped his medications, the pseudotumor enlarged with new development of recurrent pleural effusions. He was also found to have a pelvic mass that was biopsy positive for IgG4 proliferation. This case with progression to multiorgan involvement highlights the importance of identifying patients with IgG4-related disease. In contrast to previous cases with normal-to-high IgM, the IgM was low with impaired functional antibodies.